2019
DOI: 10.1016/j.bbmt.2019.01.024
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Individual versus Composite Endpoints of Acute Graft-versus-Host Disease in Determining Long-Term Survival after Allogeneic Transplantation

Abstract: The overall composite of graft-versus-host disease (GVHD)-free, relapse-free survival (GRFS), defined as survival free of grade III-IV acute GVHD (aGVHD), chronic GVHD (cGVHD) requiring systemic immunosuppressive therapy (IST), or relapse, has emerged as a useful composite in clinical trials and to capture clinically meaningful events that impact quantity and quality of survival after allogeneic hematopoietic cell transplantation (HCT). We reviewed 565 consecutive patients aged 18 years undergoing HCT for hema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…However, composite end points using right-censored data only measure the time to the first event and GRFS can't replace OS, RFS or GVHD. Magenau et al reported that chronic GVHD had less modulating effect on OS than grade III-IV acute GVHD or relapse 39 . This is partly explained by the association of graft-versus-leukemia effect with chronic GVHD 40 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, composite end points using right-censored data only measure the time to the first event and GRFS can't replace OS, RFS or GVHD. Magenau et al reported that chronic GVHD had less modulating effect on OS than grade III-IV acute GVHD or relapse 39 . This is partly explained by the association of graft-versus-leukemia effect with chronic GVHD 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Magenau et al reported that chronic GVHD had less modulating effect on OS than grade III-IV acute GVHD or relapse. 39 This is partly explained by the association of graft-versus-leukemia effect with chronic GVHD. 40 On the other hand, chronic GVHD has tremendous negative impact on quality of daily life after transplantation even under mild to moderate symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…CGRFS has been recognized as a useful addition to the existing survival functions [11][12][13] and considered as suitable implication of transplant success [14]. Our clinical paper did not include interval estimation, which is critical for assessing precision of CGRFS estimates.…”
Section: Introductionmentioning
confidence: 99%